Mary Poppins opens the door - Travers, P. L. (Pamela L.) 1906-; Shepard, Mary 1909-.; Sims, Agnes (New York Harcourt, Brace & World, 1943)
Mary Poppins returns to the Banks family in a rocket and involves the Banks children in more magical adventures including those with Peppermint Horses, the Marble Boy, and the Cat that Looked at the King.
Keywords: Fantasy